1983
DOI: 10.1002/qua.560230215
|View full text |Cite
|
Sign up to set email alerts
|

SCF and MCSCF Study of CO2 with bond angle variation

Abstract: Multiconfipuration ( M C ) S C F calculations are reported for COz for bond angles bctween 60" and 180'. The ground state configuration is found to be.. .5af46:lb:laf for small bending angles and.. -6 a~3 b j l b~l a~ for large bending angles, the change in ground state character occurring at a bond angle of about 1 0 0 O . The force constant for bending obtained from the MC-SCF function is about 8.0% lower than the corrcsponding S C F value, and in considerably better agreement with experiment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1987
1987
2000
2000

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Some previous calculations [4,30,31] did not explore the 4 -range at sufficiently small values for finding the bent minimum. A three-configuration MCSCF calculation [3] in which the 0-C-0 angle was varied from 60" to 180" missed the bent minimum because the C-0 distance was kept constant at the equilibrium value (1.162 A) of the linear species. Only Feller et al [29] and Xantheas et al [26] have previously reported the bent minimum.…”
Section: The Ring Minimummentioning
confidence: 99%
“…Some previous calculations [4,30,31] did not explore the 4 -range at sufficiently small values for finding the bent minimum. A three-configuration MCSCF calculation [3] in which the 0-C-0 angle was varied from 60" to 180" missed the bent minimum because the C-0 distance was kept constant at the equilibrium value (1.162 A) of the linear species. Only Feller et al [29] and Xantheas et al [26] have previously reported the bent minimum.…”
Section: The Ring Minimummentioning
confidence: 99%